2020
DOI: 10.3390/ijms21217961
|View full text |Cite
|
Sign up to set email alerts
|

A Human Periodontal Ligament Fibroblast Cell Line as a New Model to Study Periodontal Stress

Abstract: The periodontal ligament (PDL) is exposed to different kinds of mechanical stresses such as bite force or orthodontic tooth movement. A simple and efficient model to study molecular responses to mechanical stress is the application of compressive force onto primary human periodontal ligament fibroblasts via glass disks. Yet, this model suffers from the need for primary cells from human donors which have a limited proliferative capacity. Here we show that an immortalized cell line, PDL-hTERT, derived from prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…A major limitation of this study was the implementation of the immortalised PDL cell line, rather than primary PDL cells. Previous studies demonstrated the PDL phenotype stability of the cell line (Docheva et al, 2010) as well as its successful use as a PDL model in vitro (Ern et al, 2017;Hsieh et al, 2016;Weider et al, 2020). Moreover, the PDL-hTERT cells were capable of forming tendon/ligament-like tissues in vivo when implanted as cell pellets in a rat Achilles tendon defect model (Hsieh et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A major limitation of this study was the implementation of the immortalised PDL cell line, rather than primary PDL cells. Previous studies demonstrated the PDL phenotype stability of the cell line (Docheva et al, 2010) as well as its successful use as a PDL model in vitro (Ern et al, 2017;Hsieh et al, 2016;Weider et al, 2020). Moreover, the PDL-hTERT cells were capable of forming tendon/ligament-like tissues in vivo when implanted as cell pellets in a rat Achilles tendon defect model (Hsieh et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…collagen Johansson, 2019; Vo et al, 2020). Epidemiological studies suggest that over 50 % of the adult population is suffering from periodontitis (Romandini et al, 2021).…”
Section: Col14a1mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it was shown that the hPDLF response to mechanical stress is associated with an expression of inflammatory markers and enhanced cytokine production [27]. To confirm the effectiveness of the used in vitro compressive force model, several inflammatory markers were investigated by real-time (RT) qPCR analysis.…”
Section: Cell Cycle and Restructuring Affected On Mrna And Protein Level In Mechanically Stimulated Hpdlfsmentioning
confidence: 99%
“…Mechanical stimuli, initially directed to the ECM of the PDL, are transduced via mechanosensitive receptors, ion channels [ 7 ] and pattern recognition receptors (PRR) to biochemical responses. This leads to a local sterile inflammation with pro-inflammatory cytokines, e.g., interleukins (IL-6, IL-8) [ 8 , 9 , 10 ], vascular endothelial growth factor (VEGF) [ 11 ] and matrix metalloproteinases (MMP8 and 9) [ 10 , 12 ]. MMPs are a group of enzymes that in concert are responsible for the degradation of most extracellular matrix proteins during organogenesis, growth and normal tissue turnover and increase significantly in various pathological conditions [ 13 ] and serve to accurately predict the level of inflammation during OTM [ 14 ].…”
Section: Introductionmentioning
confidence: 99%